Impact of antibiotic de-escalation on hospitalized patients with urinary tract infections: A retrospective cohort single center study - Hanan Alshareef; Wafa Alfahad; Abeer Albaadani; Huda Alyazid; Ruba Bin Talib (Elsevier, 2020)
Background: Urinary tract infections (UTIs) can be caused by multiple drug-resistant bacteria. Empirical broad-spectrum antibiotics help minimize the risk of disease progression. Although antibiotic de-escalation is important to reduce resistance, adverse drug effects, and costs, few studies have evaluated the impact of antibiotic de-escalation on complicated UTIs in hospitalized patients. Methods: In this retrospective cohort single center observational study conducted over a period of 1 year at Prince Sultan Military Medical City (PSMMC), the rate of antibiotic de-escalation following reporting culture and sensitivity results, hospital length of stay (LOS), and factors associated with antibiotic de-escalation failure were determined. Results: Ninety-one patients were enrolled in this study. Baseline characteristics were comparable between groups. The rate of successful de-escalation was 29.7% (27 patients) while 70.3% (64 patients) failed to experience de-escalation. The median hospital LOS was significantly lower in successfully de-escalated patients, at 3 days interquartile range (IQR) (2-6), while in the failed group it was 10 days IQR (6-21) (p < 0.001). However, the identified factor associated with failure was a multidrug-resistant (MDR) pathogen that was significantly higher in the failed group than in the successful group: 38 patients (59.4%) versus 6 patients (22.2%; p < 0.001), respectively. Conclusion: Antibiotic de-escalation is an essential antimicrobial stewardship strategy. The findings of this study showed that de-escalation was associated with better patient outcomes (i.e., reduced hospital LOS) in patients admitted due to UTIs. In this study's site hospital, there is a potential for improving the current de-escalation rate. MDR pathogens were the only significant reason identified for de-escalation failure. Further data are needed on the large scale to evaluate reasons for de-escalation failure.